Statin adherence and risk of acute cardiovascular events among women: accounting for time-dependent confounding affected by previous adherenece - Lavikainen P; Helin-Salmivaara A; Eerola M; Fang G; Hartikainen J; Huupponen R; Korhonen MJ (BMJ PUBLISHING GROUP, 2022)
Objectives Previous studies on the effect of statin adherence on cardiovascular events in the primary prevention of cardiovascular disease have adjusted for time-dependent confounding, but potentially introduced bias into their estimates as adherence and confounders were measured simultaneously. We aimed to evaluate the effect when accounting for time-dependent confounding affected by previous adherence as well as time sequence between factors.
Design Retrospective cohort study.
Setting Finnish healthcare registers.
Participants Women aged 45-64years initiating statin use for primary prevention of cardiovascular disease in 2001-2004 (n=42807).
Outcomes Acute cardiovascular event defined as a composite of acute coronary syndrome and acute ischaemic stroke was our primary outcome. Low-energy fractures were used as a negative control outcome to evaluate the healthy-adherer effect.
Results During the 3-year follow-up, 474 women experienced the primary outcome event and 557 suffered a low-energy fracture. The causal HR estimated with marginal structural model for acute cardiovascular events for all the women who remained adherent (proportion of days covered 80%) to statin therapy during the previous adherence assessment year was 0.78 (95% CI: 0.65 to 0.94) when compared with everybody remaining non-adherent (proportion of days covered <80%). The result was robust against alternative model specifications. Statin adherers had a potentially reduced risk of experiencing low-energy fractures compared with non-adherers (HR 0.90, 95% CI 0.76 to 1.07).
Conclusions Our study, which took into account the time dependence of adherence and confounders, as well as temporal order between these factors, is support for the concept that adherence to statins in women in primary prevention decreases the risk of acute cardiovascular events by about one-fifth in comparison to non-adherence. However, part of the observed effect of statin adherence on acute cardiovascular events may be due to the healthy-adherer effect.